First record of White-rumped Sandpiper (Calidris fuscicollis) at Esperanza/Hope Bay, Antarctica - Silvestro, Anahí Mariel; Santos, Maria Mercedes; Juares, Mariana Alejandra; Libertelli, Marcela Mónica; Hidalgo, Keila E.; Kass, Nicolás Ariel; Casaux, Ricardo Jorge (Polar Biology)
The White-rumped Sandpiper (Calidris fuscicollis) (Vieillot 1819) is one of the longest migrating birds that breeds in the high Arctic in Alaska and Canada and spends the post-breeding period in South America. This bird is a frequent vagrant visitor of Islas Georgias del Sur/South Georgia and the South Shetland islands. Here we provide the first record for the White-rumped Sandpiper at the Continental Antarctica. The individual was observed the 2 February 2019 at Esperanza/Hope Bay (63° 23′ 56″ S, 56° 59′ 06″ W), the north of the Antarctic Peninsula, in an ice-free rockery close to a melt-water-run-off area. At the moment of the observation, the temperature was above 0 °C and the wind calm. However, strong winds from the north-west and west directions were registered during the last week of January 2019 at Esperanza Station (peak 65 knots) and at the Drake Passage (peak 49 knots) which might explain the presence of the White-rumped Sandpiper individual at Hope Bay. Our report contributes to list the non-native species observed in Antarctica. One plausible explanation could be related to changes in migratory routes of flying birds. Fil: Silvestro, Anahí Mariel. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Patagonia Norte. Centro de Investigación Esquel de Montaña y Estepa Patagóica. Universidad Nacional de la Patagonia "San Juan Bosco". Facultad de Ciencias Naturales - Sede Esquel. Centro de Investigación Esquel de Montaña y Estepa Patagónica; Argentina Fil: Santos, Maria Mercedes. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Relaciones Exteriores y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino. Departamento de Biología de Predadores Tope; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo; Argentina Fil: Juares, Mariana Alejandra. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Ministerio de Relaciones Exteriores y Culto. Dirección ...